The role of Midwives in Managing Pregnant Women’s Anxiety Levels during HIV Testing: A Phenomenological Study - Hasnia Hasnia; Yustika Rahmawati Pratami; Wiwit Vitania; Tiyan Febriyani Lestari; Nasrianti Nasrianti; Fenska Narly Makualaina (Indonesian Journal of Global Health Research, 2026)
Pregnant women can be at risk of contracting HIV/AIDS because based on age range, the highest number of HIV/AIDS cases are at the age of 25-49 years, and if based on employment status, the second highest number is housewives because... they have had sexual intercourse before, so the risk of infection is high. This study aims to to explore in depth the role of midwives in managing the anxiety levels of pregnant women undergoing HIV tests. The method in this study is a qualitative research type with an exploratory phenomenology approach. Participants in this study were midwives who provided HIV examination services to pregnant women as many as 2 people with the Colaizzi approach. The results found that midwives have an important role in providing services to manage the anxiety levels of pregnant women undergoing HIV tests. Public trust tends to be more towards midwives who have worked for a long time, because they assume that midwives who have worked for a long time have experience, but there are still some mothers who refuse and become Inhibitors then the approach to provide psychological support that can reduce anxiety, shame and fear by providing motivation , deeper support especially family such as husband and parents, so that pregnant women are willing to take an HIV test . It is concluded that there is a relationship between family support and behavior in taking an HIV/AIDS test, because in facing health problems, each individual needs family and motivation from within themselves.